Legal Assistance for the Poor in Rokan Hulu District of Riau Province - Nofrizal, Nofrizal (The Indonesian Journal of International Clinical Legal Education, 2019)
The emergence of Law No. 16 of 2011 on legal aid is expected to realizethe right society in obtaining justice. Empirically, it is known that thelaw is enjoyed by many people who has the ability to pay a lawyer oradvocate only. While the poor or who are not able to tend to resignwith the circumstances, so that the term appears that we often hear, theblunt law upward, sharp down. In Rokan Hulu district of Riau Provincethe district government together with the DPRD welcomed The lawimmediately drew up local regulations on legal aid for the poor. It isstated in the rules of the Regional Regulation Rokan Hulu No. 6 onlegal aid for the poor, but which became constraint is that in the areastill minimal LBH (Legal Aid Institutions) are eligible to give advocacyfor the poor in accordance with the requirements requested by thegovernment, the Legal Aid Institute who has been accredited by theMinistry of Law and Human Rights, and accredited by the Ministry ofJustice and Human Rights many conditions must be met so that whenthere is a credible Legal Aid Institution in the area want provide legalassistance to the poor, but cannot be done because of being knockedby requirements required by the government. The hope is that theaspirations of our country in realizing the rights of society in obtainingthis justice can be achieved, it needs further arrangements that lead toit the implementation of legal aid programs for these poorcommunities by taking into account the quantity of legal institutionsthere are and many conflicts that need to be given advocacy assistancefor these incapable people.